2001
DOI: 10.1006/jmbi.2001.5084
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the liganded SCP-2-like domain of human peroxisomal multifunctional enzyme type 2 at 1.75 Å resolution 1 1Edited by R. Huber

Abstract: b-Oxidation of amino acyl coenzyme A (acyl-CoA) species in mammalian peroxisomes can occur via either multifunctional enzyme type 1 (MFE-1) or type 2 (MFE-2), both of which catalyze the hydration of trans-2-enoylCoA and the dehydrogenation of 3-hydroxyacyl-CoA, but with opposite chiral speci®city. MFE-2 has a modular organization of three domains. The function of the C-terminal domain of the mammalian MFE-2, which shows similarity with sterol carrier protein type 2 (SCP-2), is unclear. Here, the structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 50 publications
(56 reference statements)
6
74
0
Order By: Relevance
“…Each of the four variants, regardless of the presence or absence of either presequence or PTS1, were found by far-UV CD to be natively folded, as estimated by far-UV CD and confirming previous structural data [3,13,26,[29][30][31]. Previous spectroscopic studies [32,33] have shown that the presequence of SCP2 does not display regular secondary structure-a conclusion confirmed by the CD data presented here.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Each of the four variants, regardless of the presence or absence of either presequence or PTS1, were found by far-UV CD to be natively folded, as estimated by far-UV CD and confirming previous structural data [3,13,26,[29][30][31]. Previous spectroscopic studies [32,33] have shown that the presequence of SCP2 does not display regular secondary structure-a conclusion confirmed by the CD data presented here.…”
Section: Discussionsupporting
confidence: 90%
“…[26,30,31] in which the C-terminal segment of SCP2 is found to be in a coiled conformation. Crystal structures of liganded SCP2 [13,29] show the C-terminal segment adopting an a-helical structure ''capping'' the ligand binding pocket. This coil-helix transition upon ligand binding may to some degree explain the ''tightening'' of secondary structure we observe when SCP2 is loaded with stearoyl CoA.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid binding site utilized by all four ligands tested overlaps well with the hydrophobic cavity ( Figure 1A) and is consistent with the location of the phenyl moiety of Triton or C11-C16 of palmitic acid bound to SCP2 ( Author Manuscript (10,11). This central binding cavity likely represents a high-affinity target site that has general binding affinity for hydrophobic ligands (28).…”
Section: Chemical Shift Perturbation Mappingsupporting
confidence: 69%
“…Our NMR relaxation data ( Figure 4E,F, Supporting Information Figure 7) provide direct evidence for the presence of conformational flexibility (at picosecond to nanosecond time scales) in the SCP2 peptide backbone, which is also hinted by elevated X-ray B-factors in the C-terminal part of the SCP2 structures (10,13). Moreover, the CPMG/HSQC experiments ( Figure 5) indicate the presence of backbone dynamics also at slow (microsecond to millisecond) time scales.…”
Section: Conformational Dynamics Of α-Helices Framing the Lipid Bindimentioning
confidence: 63%
See 1 more Smart Citation